Decline in Hand Bone Mineral Density Indicates Increased Risk of Erosive Change in Early Rheumatoid Arthritis. Issue 4 (April 2014) - Black, R. J.; Spargo, L.; Schultz, C.; Chatterton, B.; Cleland, L.; Lester, S.; Hill, C. L.; Proudman, S. M.
<x xml:space="preserve">Abstract</x> Objective Despite better disease suppression with combination disease‐modifying antirheumatic drugs (DMARDs), some patients with rheumatoid arthritis (RA) have progressive erosive disease. The objective of this study was to determine whether hand bone mineral density (BMD) loss in the first 6 months of treatment indicates increased risk of erosions at 12 months. Methods Patients with DMARD‐naive early RA receiving treat‐to‐target therapy were studied (n = 106). Hand BMD was measured at baseline and 6 months by dual x‐ray absorptiometry. Hand and feet radiographs were performed at baseline and 12 months and scored using the van der Heijde modification of the Sharp method. A K‐means clustering algorithm was used to divide patients into 2 groups: the BMD loss group or the no loss group, according to their absolute change in BMD from baseline to 6 months. Multiple regression analysis (hurdle model) was performed to determine the risk factors for both erosive disease and erosion scores. Results Hand BMD loss at 6 months was associated with erosion scores at 12 months (P = 0.021). In a multiple regression analysis, hand BMD loss (P = 0.046) and older age at onset (≥50 years; P = 0.014) were associated with erosive disease, whereas baseline erosion scores (P = 0.001) and anti–cyclic citrullinated peptide (P = 0.024) were correlated with erosion severity/progression. Conclusion In RA patients receiving treat‐to‐target therapy, early hand BMD loss could identify patients who are at risk of developing erosive disease at 12 months, potentially allowing intensification of treatment to prevent erosive damage.